Documenting the modeling process with a standardized data structure described and implemented in DynamicVu. (30th August 2022) - Farr, Warren W.; Allen, Samuel D.; Tomoaia‐Cotisel, Andrada; Hovmand, Peter S.
Abstract: Documenting the process of building a simulation model is different from documenting the simulation model itself. Good model‐building practice includes the discovery of potentially large sets of multimedia data. Organizing and documenting data and the process of collecting it has several advantages including: tightly linking data to its source and the timing of its discovery; separating source data from researcher inference (allowing for independent inspection); maintaining an evolutionary timeline; and easily sharing source data among participants and researchers. The topic of documenting models has been widely discussed. In contrast, this article proposes a data structure and its methods for documenting the process of building a simulation model. © 2022 System Dynamics Society.